THU0716-HPR The impact of exercise on sleep in people with rheumatoid arthritis: a pilot randomised controlled trial. (12th June 2018) - Mckenna, S.G.; Donnelly, A.; Appel Esbensen, B.; Comber, L.; Ng, W.L.; Maqsood, A.; Fraser, A.; Kennedy, N.
Abstract : Background: Reduced sleep duration and poor sleep quality are prevalent complaints in rheumatoid arthritis (RA). These in turn may further deteriorate functional ability and reduce the person's exercise levels. Current rheumatology guidelines recommend exercise as a key component in the management of RA however, what is lacking is its impact on sleep. Objectives: To obtain reliable estimates regarding recruitment rates; retention; protocol adherence; adverse events, in addition to producing estimates of the potential effect sizes of the intervention on changes in outcomes of sleep duration; sleep quality and disturbances; RA related pain; depression; anxiety; functional limitation; disease activity and fatigue. Methods: Participants were recruited in person at weekly rheumatology clinics at a University Hospital and through self-selected social networking. They were randomised to either a walking based exercise intervention consisting of 28 walking sessions, with 1 per week being supervised by a trained physiotherapist, spread over 8 weeks (2–5 times/week), or a control group who received advice on the benefits of exercise for people with RA. Ethical approval was received. Descriptive statistics and t-tests were used to analyse the data with SPSS v22. Results: One hundred and one (101) people were identified through the rheumatology clinics, with 36 contacting the primary investigator through social networking. Of these, 24 met the eligibility criteria, with 20 being randomised (18% recruitment; 100% female; mean age 57 (SD 7.3 years). Ten exercise participants (100%) and 8 controls (80%) completed final assessments, with both groups being equivalent for all variables at baseline. Exercise participants completed 87.5% of supervised sessions and 93% of unsupervised sessions. No serious adverse events were recorded and through semi-structured interviews the intervention was highly acceptable to exercise participants. Pittsburgh Sleep Quality Index (PSQI) global score showed a significant mean improvement between the exercise group −6.6 (SD 3.3) compared to control −0.25 (SD 1.1) (p=0.012); PSQI subcomponent sleep duration showed a significant improvement in mean hours between the exercise group 1.65 (SD 0.39) and control 0.56 (SD 0.46) (p=0.021); PSQI subcomponent sleep quality indicated those in the exercise group improved their sleep quality from fairly bad/poor to fairly good/very good, while those in control reported no change at fairly bad/poor. Global rating of change indicated exercise participants reporting their sleep was minimally/much improved, while control participants reported no change/minimally worse, post intervention. Conclusions: The walking based exercise intervention designed to improve sleep was feasible, safe and highly acceptable to study participants, with those participants in the exercise group reporting improvements in sleep duration and sleep quality compared to the control group. Adverse events were predominantly mild. This pilot provides a framework for larger intervention studies and based on these findings a fully powered trial of walking as an exercise based intervention is recommended, preceded by focus groups to investigate methods to improve recruitment of males. Disclosure of Interest: None declared